Reduced striatal dopamine transmission in REM sleep behavior disorder comorbid with depression. (3rd February 2015) - Wing, Yun Kwok; Lam, Siu Ping; Zhang, Jihui; Leung, Eric; Ho, Chi Lai; Chen, Sirong; Cheung, Man Ki; Li, Shirley Xin; Chan, Joey Wing Yan; Mok, Vincent; Tsoh, Joshua; Chan, Anne; et al.
Abstract : Objective: To investigate dopamine transmission in patients with comorbid REM sleep behavior disorder (RBD) and major depressive disorder (MDD). Methods: This is a case-control study including 11 medicated patients with comorbid RBD and MDD (mean age 47.5 ± 8.2), 8 medicated patients with MDD only (mean age 47.9 ± 8.4), and 10 healthy participants (mean age 46.5 ± 10.6 years). They underwent clinical assessment, video-polysomnography, olfactory tests, and neuroimaging studies ( 18 F-DOPA, 11 C-raclopride, and 18 F-FDG PET neuroimaging). Results: Compared with the 2 control groups, patients with comorbid RBD and MDD had significantly lower 18 F-DOPA uptake at 60 minutes in the putamen and caudate after controlling for age and sex effect ( p < 0.05). There were no significant differences for the 11 C-raclopride and 18 F-FDG-PET. The 18 F-DOPA uptake in putamens had significant inverse correlation with severity of RBD symptoms ( p < 0.01) and REM-related tonic muscle activity ( p < 0.01). The comorbid RBD and MDD group had more impairment in olfactory function. Conclusion: Patients with comorbid RBD and MDD had presynaptic dopamine dysfunction and impaired olfactory function. There is a distinct possibility that the development of RBD symptoms among patients with MDD may represent an early phase of α-synucleinopathy neurodegeneration instead of a merely antidepressant-induced condition.